The effect of platelet-rich fibrin on the acceleration of osteoblast proliferation after endosseous dental implant insertion - Evan Chandra; Suparyono Saleh; Murti Indrastuti (Majalah Kedokteran Gigi Indonesia, 2020)
The osseointegration process of dental implants begins with osteoblast differentiation and proliferation, which is an important aspect of the bone regeneration process. Platelet-rich fibrin (PRF) is a platelet that contains a large amount of fibrin and growth factor, which is widely used to accelerate bone regeneration. This study aims to determine the effect of PRF on the acceleration of osteoblast proliferation after endosseous dental implant insertion. Twelve male Wistar rats weighing 250 to 300 gr of 8 to 15 weeks as an animal model were divided into two groups, the control group and treatment group, based on days and PRF treatment. Three ml of Wistar rat blood was obtained and centrifuged for 12 minutes at a speed of 2700 rpm to make PRF. Afterward, platelet-rich fibrin was applied to implant bed, and the dental implant was inserted at the lateral epicondyle of the right femur in 3 mm depth and 1.8 mm diameter dimension. Incontrol groups, dental implants were immediately inserted after implant bed preparation without PRF administration. Observation of the Wistar rats was carried out on days 14 and 28 for each group. The rats were terminated accordingto the timeline of group design. The epicondylus lateralis femoris dextra bone of the rats was taken and fixed with 10% buffered formalin solution. Then, histological samples were made with hematoxylin-eosin staining. Sample observation was done under a light microscope to calculate the number of osteoblasts. The data were analyzed using the two-way ANOVA test, followed by LSD post hoc test. Based on the two-way ANOVA test, there was a significant difference between control groups and treatment groups (p<0.05), and there were significant differences between the observation result of days 14 and 28 (p<0.05). The application of PRF increased osteoblast proliferation for the first 14 days, but the rate decreased after that. Based on the LSD post hoc test, there were differences in osteoblast proliferation between the treatment and control group (p<0.05). Thus, it is concluded that platelet-rich fibrin increased the acceleration ofosteoblast proliferation after endosseous dental implant insertion.